Penerapan Community Based Tourism Dalam Pengelolaan Daya Tarik Wisata Pantai Lon Malang Kabupaten Sampang - Aprilia, Tri Utami; Idialis, Alifah Rokhmah (JURNAL DESTINASI PARIWISATA; Vol 10 No 2 (2022): VOL 10, NO 2 (2022): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2022.v10.i02.p04, 2023)
Community Based Tourism is a tourism concept that makes the community the subject of tourism development. Lon Malang Beach is one of the priority tourist destinations in Sampang Regency that applies this community-based tourism concept. This research aims to see how the application of the principles of Community Based Tourism in Lon Beach Malang and see how the role of stakeholders involved in tourism development. This research uses a qualitative descriptive approach with data collection methods in the form of observation, interviews, and documentation. The subjects in this study using purposive sampling techniques. The results of this study show that the development of Lon Malang beach tourism has applied the principle of Community Based Tourism, where full tourism management is carried out by local communities through village institutions such as POKDARWIS and BUMDes. The results of the study also show that stakeholders have played a role in the development of Lon Malang beach tourism and cooperate with each other. Keywords: Community Based Tourism, Tourism, Community Participation, Stakeholders